Heat treatment of milk: Effect on concentrate viscosity, powder manufacture and end-product functionality. (May 2022) - McCarthy, Noel A.; Magan, Jonathan B.; Kelleher, Clodagh M.; Kelly, Alan L.; O'Mahony, James A.; Murphy, Eoin G.
Abstract: The heat treatment (HT) of milk and dairy ingredients for the purpose of powder manufacture is a complex and multifaceted area, with many factors influencing microbial quality, process efficiency (e.g., product composition, processing equipment and operating parameters) and end-powder functionality (e.g., heat stability, powder rehydration, gelation, etc.). One primary area of research is the mechanisms responsible for heat-induced viscosity development, mainly due to its role in fouling of processing equipment. Developing a means of predicting viscosity increase due to thermal heat treatment have proven beneficial and are discussed herein. The review also highlights scientific areas of interest where limited published information exists, and perhaps should be explored in the near future.